The power of CEO growing up in poverty: Enabling better corporate environmental, social, and governance (ESG) performance - Liu, Yang; Zhang, Han; Zhang, Fukang (Corporate social-responsibility and environmental management, 2024)
Recently, environmental, social, and governance (ESG) has been the subject of extensive research and publication. Researchers have pointed out that corporate ESG performance is not only determined by the demographic and personality characteristics of current executives, but also by early‐life experiences. Recent research has illuminated the influence that early‐life experiences of executives have on corporate social performance. However, there is still a lack of research on how executive poverty experiences affects corporate ESG performance. To fill this void, our study investigates the potential influence of CEOs' childhood poverty experiences on corporate ESG performance, employing the upper echelon theory and imprinting theory. Specifically, we gathered data for publicly traded Chinese companies from 2011 to 2020, and discovered that companies helmed by CEOs who grew up in underprivileged neighborhoods demonstrated superior ESG performance. We also scrutinized the moderating mechanisms that impacted the strength and attenuation of poverty imprinting. Our findings reveal that CEO expected tenure and green investors augment the favorable impact of poverty imprinting on corporate ESG performance, while CEOs who receive higher compensation exhibit a weaker imprint. Our study contributes significantly to the imprinting field and the literature on corporate ESG performance, while also providing valuable insights into strategies that facilitate pro‐social conduct among firms.